Donald T. Campbell's Evolutionary Perspective and its Implications for Evaluation - Robert Picciotto (The Evaluation Center at Western Michigan University, 2019)
Background: Donald T. Campbell, a scientist, humanist, and generalist, left an indelible mark on the evaluation discipline through his methodological work. He is less well known within the evaluation community for his landmark contributions to biology and philosophy. Yet, the evolutionary epistemology that he pioneered has significant implications for evaluation.     Purpose: This article examines the relevance of Donald T. Campbell's blind variation and natural selection approach to evaluation theory, including an elucidation of its basic logic, its social remit as a discipline and trans-discipline, and its summative and formative functions. It also sketches in broad strokes the implications of evolutionary thinking for evaluation practice, including natural and artificial selection, ontogeny, phylogeny, co-evolution, and feedback. Finally, it comments on Campbell's Experimenting Society vision and  the ongoing craze for randomised evaluations in development through an evolutionary lens.   Setting: Not applicable.   Intervention: Not applicable.   Research Design:  Not applicable.   Data Collection and Analysis: Not applicable.   Findings: Not applicable.